Global Marketing Management / Fourth Edition - Keegan Warren J (Prentice Hall International, 1989)
Preface, A Conceptual Overview, Analyzing the Global Marketing Environment, Formulating Multinational Marketing Strategies, Marketing the Multinational Marketing Program, Appendices, Index.
Preface, A Conceptual Overview, Analyzing the Global Marketing Environment, Formulating Multinational Marketing Strategies, Marketing the Multinational Marketing Program, Appendices, Index.